Understanding the Structural, Human Resource, Political, and Symbolic Dimensions of Implementing and Sustaining Interprofessional Education. - Lawson, Jonathan; Farnsworth, Tracy J.; Peterson, Ten; Neill, Karen; Neill, Mark; Seikel, John A. (Tony) (Journal of Allied Health)
This study investigated the perceptions of deans and faculty members of the Association of Schools of Allied Health Professions (ASAHP) concerning the degree to which their institutions' implement and integrate the structural, human resource, political, and symbolic frames or dimensions of interprofessional education (IPE). The study identified correlations among these frames/dimensions, including their relationship with overall IPE program progress and success. METHODS: This study utilized a nonexperimental comparative descriptive and correlational survey design. The instrument was developed by the researchers and administered online using a readily accessible data collection process. Data were analyzed using descriptive and inferential statistics. Content validity and reliability were established prior to full implementation of the survey. RESULTS: Results revealed high levels of interest but lower levels of progress and success in implementing the various frames/dimensions of IPE. Strong correlations existed between the structural, human resource, political, and symbolic dimensions of IPE, and these dimensions individually and collectively predicted overall IPE program progress and success. CONCLUSION: The differences between interest and performance raised important questions and led to conclusions about leadership effectiveness, organizational clarity, and the process of implementing the organizational change needed for effective IPE at ASAHP institutions.